2021
DOI: 10.1007/s40265-021-01528-8
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Sphingosine-1-Phosphate Signaling in Immune-Mediated Diseases: Beyond Multiple Sclerosis

Abstract: Sphingosine-1-phosphate (S1P) is a bioactive lipid metabolite that exerts its actions by engaging 5 G-protein-coupled receptors (S1PR1-S1PR5). S1P receptors are involved in several cellular and physiological events, including lymphocyte/hematopoietic cell trafficking. An S1P gradient (low in tissues, high in blood), maintained by synthetic and degradative enzymes, regulates lymphocyte trafficking. Because lymphocytes live long (which is critical for adaptive immunity) and recirculate thousands of times, the S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 131 publications
(253 reference statements)
0
82
0
5
Order By: Relevance
“…In 2019, the FDA approved Siponimod, an inhibitor selective for S1PR1 and S1PR5, which has shown effectiveness in MS treatment (U.S. Food and Drug Administration, 2019;Fronza et al, 2021). Ozanimod was approved for use in MS in 2020, and is selective for S1PR1 and S1PR5 as well (U.S. Food and Drug Administration, 2020; Fauzyah et al, 2021;Perez-Jeldres et al, 2021). In March 2021, Ponesimod, a highly selective inhibitor of S1PR1, was approved for patients with relapsing MS (Fronza et al, 2021;U.S.…”
Section: Drugs and Treatments Targeting Lipid Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2019, the FDA approved Siponimod, an inhibitor selective for S1PR1 and S1PR5, which has shown effectiveness in MS treatment (U.S. Food and Drug Administration, 2019;Fronza et al, 2021). Ozanimod was approved for use in MS in 2020, and is selective for S1PR1 and S1PR5 as well (U.S. Food and Drug Administration, 2020; Fauzyah et al, 2021;Perez-Jeldres et al, 2021). In March 2021, Ponesimod, a highly selective inhibitor of S1PR1, was approved for patients with relapsing MS (Fronza et al, 2021;U.S.…”
Section: Drugs and Treatments Targeting Lipid Metabolismmentioning
confidence: 99%
“…While S1P pathway modulators have been used in MS for some time, recent studies have begun to demonstrate efficacy in different pathologies such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), psoriasis, and inflammatory bowel disease (IBD) including ulcerative colitis (UC), and Crohn's disease (CD) (Perez-Jeldres et al, 2021). A clinical trial with Ozanimod showed effectiveness in the treatment of moderate to severe UC (Sandborn et al, 2016;Perez-Jeldres et al, 2021). Other medications that are not currently approved have undergone trials in the treatment of IBD with varying degrees of success; these drugs include Mocravimod, Etrasimod, and Amiselimod (Perez-Jeldres et al, 2021).…”
Section: Drugs and Treatments Targeting Lipid Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…While this strategy is highly efficient in autoimmune CNS diseases such as MS, it may yield beneficial effects in inflammatory bowel diseases as well. Indeed, several preclinical studies have examined these modes of actions and may provide useful in future clinical approaches [40][41][42]. Neurodegeneration is a frequent consequence of severe neuroinflammation in MS.…”
Section: Introductionmentioning
confidence: 99%